Undergraduate Students’ Difficulties in Translating an Editorial of the Jakarta Post - Putri, Fegi Kurniawan Dwi; Mukhrizal, Mukhrizal; Zahrida, Zahrida (Journal of English Education and Teaching, 2024)
The objective of this research was to find out the students’ dominant difficulties in translating an editorial text of The Jakarta Post. The subjects of this research were 30 seventh semester students of Education Study Program at Universitas Bengkulu in the academic year 2020/2021. This research used a quantitative descriptive method. The data were collected with a questionnaire and were counted in percentage terms. The results of this research showed that there were 5 students’ dominants difficulties in translating the editorial, i.e. a.)The difficulties in understanding unfamiliar words(60%), b.) The difficulties in understanding the texts although they understand the meaning of the words but they could not understand it coherently. Sometimes one sentence looked like disconnected with another sentence so it became odd (57%),c.)The difficulties in understanding the difficult sentences (47%), d.)The difficulties in translating the words that had multiple meanings which made it difficult for them to determine which meaning was correct and in understanding the ambiguous words (43%), and e.)The difficulties in translating phrases (43%). In conclusion, among all the dominant difficulties in translating the editorial the most dominant one was the difficulties in understanding unfamiliar words (60%). It was suggested that the undergraduate students should study lexicology and syntax intensively.